EKSPLORASI ETNOMATEMATIKA PADA BATIK GEDOG - Lia Listiana Wati; Afdiyatul Mutamainah; Lilis Setianingsih; Mu'jizatin Fadiana (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2021)
Ethnomatematics is a study that contains mathematical ideas from traditional societies which are applied to certain societies which are practiced by cultural groups. One of the existing cultures in Tuban district is Gedog batik. Gedog batik ethnomatematics is a study that examines the application of mathematical concepts to Gedog batik. The purpose of this research is to examine how the mathematical concepts of the Gedog batik motif. The method used in this research is exploration with an ethnographic approach. The results showed that the Gedog batik motif contains mathematical elements, including the concepts of symmetry, transformation (reflection, translation, rotation) and congruence. By knowing the mathematical elements of Gedog batik, it is hoped that it can help understand mathematical concepts based on contextual problems that arise in the Gedog batik culture.